2022
DOI: 10.2147/idr.s339761
|View full text |Cite
|
Sign up to set email alerts
|

Emergence of optrA-Mediated Linezolid Resistance in Enterococcus faecium: A Molecular Investigation in a Tertiary Hospital of Southwest China from 2014–2018

Abstract: Purpose: To investigate the potential mechanism and molecular characteristics of linezolidnon-sensitive Enterococcus faecium from a tertiary hospital in southwest China and characterize the relevant plasmids. Patients and Methods: Linezolid-non-sensitive Enterococcus faecium (LNSEFM) isolates collected from January 2014 to December 2018 were screened for resistant genes 23s rRNA, rplC, rplD, rplV, optrA, cfr, poxtA, by PCR. Molecular epidemiological analysis was performed by multilocus sequence typing (MLST). … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
9
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(9 citation statements)
references
References 45 publications
0
9
0
Order By: Relevance
“…It was found mainly in gram-positive bacteria, which might be associated with decreased penicillin susceptibility (Tran et al, 2011). Although we did not find vancomycin resistance genes, more attention should be given to monitoring the VRE that carries transferable oxazolidinone resistance genes (Yi et al 2022). A total of 175 enterococcal isolates harbored multiple resistance genes, which indicated a broad antibiotic resistance spectrum of enterococcal isolates.…”
Section: Discussionmentioning
confidence: 62%
See 1 more Smart Citation
“…It was found mainly in gram-positive bacteria, which might be associated with decreased penicillin susceptibility (Tran et al, 2011). Although we did not find vancomycin resistance genes, more attention should be given to monitoring the VRE that carries transferable oxazolidinone resistance genes (Yi et al 2022). A total of 175 enterococcal isolates harbored multiple resistance genes, which indicated a broad antibiotic resistance spectrum of enterococcal isolates.…”
Section: Discussionmentioning
confidence: 62%
“…Enterococci in animals used for food production may contaminate food and the environment, creating a risk of human infection through anthropozoonosis ( He et al, 2016 ). Enterococcus faecalis and Enterococcus faecium often cause urinary tract and soft tissue infections, and in severe situations, they may cause septicemia or meningitis ( Yi et al, 2022 ). Notably, E. faecium and E. faecalis are important nosocomial pathogens worldwide ( Bender et al, 2018 ).…”
Section: Introductionmentioning
confidence: 99%
“…in healthcare environments. Due to its clinical and public health significance, the World Health Organization (WHO) and the U.S. Centers for Diseases Control and Prevention listed VRE as a high-priority pathogen in urgent need of drug research and development (Ayobami et al, 2020;Yi et al, 2022). Emaneini et al (2016) reported that the prevalence of vancomycin-resistant Enterococci infec-tions among Enterococcus species was 9.4% (95% C.I.…”
Section: Discussionmentioning
confidence: 99%
“…OptrA was primary mechanism in LRE that was first detected in a clinical E. faecalis from China in 2015, and was commonly localized within chromosomes or plasmids and can be transmitted through horizontal gene transfer (HGT) via mobile genetic elements such as transposons, integrative and conjugative elements, and insertion sequences [ 38 , 39 ]. The recently reported poxtA gene, mediating resistance to oxazolidinones, tetracyclines, and phenicols, was first described in an MRSA isolate from an Italian patient [ 40 ]. Yi et al reported that 46.7% (7/15) of linezolid-resistant clinical isolated E. faecium were positive for optrA , and 13.3% (2/15) of isolates had poxtA in China [ 41 ].…”
Section: Enterococcus Faeciummentioning
confidence: 99%